Capsule Endoscopy for Obscure Gastrointestinal Bleeding: A Single‑Center Experience - Chauhan, Virender; Goel, Vasudha; Jain, Mukesh; Gupta, Gaurav; Pokharna, Rupesh; Sharma, Shyam Sunder; Nijhawan, Sandeep (Journal of Digestive Endoscopy, 2018)
Background: Capsule endoscopy (CE) has an established role in evaluating obscure gastrointestinal bleeding (OGIB). The aim was to know the diagnostic yield of CE and spectrum of OGIB. Materials and Methods: In this retrospective study, we evaluated all the patients with obscure gastrointestinal bleed using MiroCam capsule endoscope (IntroMedic, Seoul, Korea) between February 2014 and March 2018. Clinical data, ancillary investigations, and response to specific treatment were considered to confirm CE findings. Results: Out of 102 patients included in the study (mean age 54.5 ± 16.1 years, male: female ratio = 1.83:1) OGIB‑overt and OGIB‑occult was present in 46 and 56 patients, respectively. Diagnostic yield of CE was similar in both the groups (overt‑37/46, 80.4% versus occult‑37/56, 66.5%) (P ≥ 0.05), although there was trend to find more lesions in overt group. Overall positive diagnostic yield was 72.5%. Lesions detected were vascular malformations in 21 (20.5%), nonsteroidal anti‑inflammatory drug enteropathy in 13 (12.7%), small bowel ulcerations in 27 (26.4%), which were further divided into three subgroups (a) nonspecific ulcerations 11 (10.7%), (b) tubercular ulcer with/without stricture in 7 (6.8%) and (c) serpiginous ulcers and fissuring with cobble‑stone appearance suggestive of Crohn’s disease in 9 (8.8%), portal hypertensive enteropathy in 5 (4.9%), worm infestation (hookworms in 3, roundworms 1) in 4 (3.9%), and small bowel tumour in 1 (0.98%) patient. Overall, 56.7% patients were having definitive (P2) lesions (Saurin classification). Two patients had retention of capsule, but none developed intestinal obstruction. Capsule was removed with surgical intervention. Conclusion: CE has high diagnostic yield, relative safety and tolerability, and it is an important diagnostic tool for OGIB. Small bowel tuberculosis, Crohn’s disease and Worm infestation continue to be commonly recognized causes of OGIB in developing countries like India.
Keywords: Capsule endoscopy; obscure gastrointestinal bleeding; small bowel